Socio-Economic Policy of Russia on Black Sea Coast of Caucasus in Second Half of 19th Century - I. M. Fedina (Научный диалог)
The problematic issues of the socio-economic policy of Russia in the development of the Black Sea coast of the Caucasus in the second half of the 19th century is analyzed in the article. The relevance of scientific research is explained not only by the growing public interest in the processes of regional history, but also by the need for scientific understanding and study of the development of the strategically important South Russian region. The localization of creative research was carried out, first of all, on insufficiently covered issues in the scientific literature, and often on historical subjects that were practically not considered by researchers. Particular attention in the study is paid to the description of the migration movement to the eastern Black Sea region and the formation of settlements. The projects of scientists, officials of various departments to improve economic development were considered. The features of land use and land management of coastal settlements are revealed. The role of the state in the development and expansion of the settlement network is characterized. It has been established that the construction of sustainable communications (highways, railways, sea routes) contributed to the consolidation of Russian influence on the Black Sea coast of the Caucasus. It is shown that communications, habitation of the lands of the coastal strip provided the resort development of the Eastern Black Sea region from the end of the 19th century. The author comes to the conclusion that the uncertainty of land use boundaries, as well as the attraction to the region of the population unfamiliar with local natural and climatic conditions, the lack of communications in every possible way slowed down the development of the region.